Pemetaan Sistematik Penerapan Literasi Digital di Indonesia Menggunakan R Biblioshiny adan VOSviewer - Tupan Tupan (Media Pustakawan, 2023)
The era of digital literacy is characterized by the ease with which users can access the information they need using a computer connected to the internet network. This study aims to determine the distribution of digital literacy research publications by year, the most productive researchers publishing digital literacy research, the most productive publishers in publishing digital literacy, the distribution of digital literacy research by country, the distribution of digital literacy research by document type, the distribution of digital literacy research by subject , the interrelationships of the three areas of digital literacy, keywords that often appear related to digital literacy topics, co-occurrence network maps, thematic map diagrams with 4 quadrants. The study was conducted using a bibliometric approach using R biblioshiny and VOSviewer software. Data collection was carried out on 26-27 August 2022 by searching using keywords (TITLE-ABS-KEY( digital AND literacy) AND TITLE-ABS-KEY (indonesia ) . The results of the analysis show that systematic mapping of digital literacy research publications in Indonesia has been carried out since 2015 and the peak will occur in 2021. The most productive researcher published the application of digital literacy Amia Luthfia from Bina Nusantara University, Jakarta. The most published document type is in the form of articles. The most productive publishers in publishing digital literacy are the Journal of Physics: Conference Series and the Horizon of Education. The most subjects are social science, computer science, Engineering, and Business, Management and Accounting. The topics of digital literacy, e-learning, digital technologies and learning systems are the most common topics in the application of digital literacy. From the thematic diagrams, the theme of human article literacy is obtained, and information use digital storage is the theme of the research being carried out.